A polyhydroxylated sterol and a saponin isolated from the starfish culcita novaeguineae - Ngoan, Bui Thi; Hong Hanh, Tran Thi; Vien, Le Thi; Diep, Chau Ngoc; Thao, Nguyen Phuong; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; et al. (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, a polyhydroxylated sterol 5α-cholestane-3β,6β,7α,8β,15α,16β,26-heptol (1) and an asterosaponin sodium salt of 6α-[(O-β-D-fucopyranosyl-(l®2)-O-β-D-galactopyranosyl-(l®4)-O-[β-D-quinovopyranosyl-(l®2)]-O-β-D-xylopyranosyl-(l®3)-O-β-D-quinovopyranosyl)oxy]-5α-pregn-9(11)-ene-20-one (2), were isolated from the methanol extract of the starfish Culcita novaeguineae. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. Compounds 1 was isolated from C. novaeguineae for the first time.